The Use of Discovery Learning Model and Authentic Material to Improve Students’ Writing Ability of Procedure Text - Rojiyah, Siti (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The ability to communicate in English, the ability to collaborate, and creativity are needed for SMK graduates, including students of the Multi Media Class. However, English language skills specifically for MM class are still lacking, around 73.46% or 7 students stated that writing is an obstacle. Therefore, Discovery Learning (DL) research using authentic materials was applied to achieve learning outcomes and determine the improvement of students’ learning outcomes, especially in composing procedure texts. Classroom action research, where each cycle has stages of planning, implementation, observation and reflection of action, was carried out at SMK Muhammadiyah Aimas through three cycles (6 meetings) involving 13 students majoring in Multi Media class X in odd semester. The teacher acted as the main researcher. Data was collected using tests and product assessment sheets. Data analysis was carried out by comparing the results in cycles I, II and III quantitatively, while observation data was investigated qualitatively. The results showed that Discovery Learning and the Use of Authentic Materials are likely to be effective in improving the learning outcomes of students in class X majoring in Multi Media. In terms of process, students felt that their learning outcomes improved from an average of 73.46 to 81.38. A score improvement was also seen in the students’ test results which increased from 46.2% in cycle I to 77.23% in cycle II, and further to 81.38% in cycle III. In conclusion, Discovery Learning and Authentic Material can be an alternative effort to create meaningful experiences in creative learning, independence, and skill in communicating orally and in writing.